Respuesta :
Answer: First option.
Step-by-step explanation:
The complete exercise is attached.
Given the following equation:
[tex]5 (x-3) + 7 (x + 4) = 73[/tex]
The steps to solve it are:
1. Apply the Distributive property:
[tex]5x-15+7x+28=73[/tex]
2. Add the like terms:
[tex]12x+13=73[/tex]
3. Subtract5 13 from both sides of the equation:
[tex]12x+13-(13)=73-(13)\\\\12x=60\\\\[/tex]
4. Divide both sides of the equation by 12:
[tex]\frac{12x}{12}=\frac{60}{12}\\\\x=5[/tex]
To verify it, let's substitute [tex]x=5[/tex] into the equation:
[tex]5 (5-3) + 7 (5 + 4) = 73[/tex]
Evaluating, we get:
[tex]5 (2) + 7 (9) = 73\\\\10+63=73\\\\73=73[/tex]
Based on this, we can determine that Sarita's solution is correct, but she made an error in her verification (Observe that [tex]5-3\neq -2[/tex])
![Ver imagen luisejr77](https://us-static.z-dn.net/files/dcc/113c717c28a9fc269346f59b430c72a1.jpg)